The Filipino “Backer System” in the Maritime Industry: The Privileged Access to Seafaring Jobs - Maido, Marjorie Ablanido (Sociologija. Mintis ir veiksmas, 2021)
Drawing from the narratives of twenty-eight global Filipino seafarers and two Crewing Managers, this paper analyzes how Bourdieu’s notion of social capital is utilized through the Filipino “backer system”. The “backer system” refers to a legitimated practice in the maritime industry where an applicant seeks a backer or a patron to recommend him to a manning agency to launch his seafaring career. This practice, however, is governed by characteristics that define the power relations among the social actors. The backer system emphasizes why strong ties matter – how the utilization of family social capital and ethnic ties mobilizes a jobseeker’s career and how prospective seafarers usually access these ties. As social capital is a network of trust and reciprocity, the Filipino value of utang na loob reflects the nature of the transaction enclosed in the “backer system”. Utang na loob refers to debt of goodwill where one who receives favor from another is morally required to return the favor. However, as polarizing as it is, the principle of utang na loob is shaped as symbolic capital and symbolic violence. As a capital, it transforms a disadvantaged position into an advantaged one, where economic and instrumental gains are received. When the transaction becomes abusive and exploitative, it becomes symbolic violence. Premised on an unequal endowment of social capital, the “backer system” reproduces inequality, where those with merit and cultural capital fail to advance their careers because their social capital is non-existent or inadequate.
Keywords: backer; social capital; social network; Filipino seafaring; ethnic ties; utang na loob